2011
DOI: 10.2174/1874428101105010001
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Factors on the Vestibular Function of Deaf Children and Adolescents - Evaluation by Means of Dynamic Posturography

Abstract: Abstract:Objectives: Previous studies have shown that both motor exercises and vestibuloocular tests reveal a difference in the balance function of deaf and normal-hearing children and adolescents.The purpose is to evaluate the influence on balance function of the hearing status. Material and Methods:A total of 80 children and adolescents between the ages of 4 and 20 years were studied. Of these, 40 children were either deaf or severely hearing impaired. The remaining 40 were control subjects of equivalent age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 34 publications
0
17
0
4
Order By: Relevance
“…As regards mechanical perturbation, instead, the most widespread test is the Sensory Organization Test (SOT, NeuroCom, Natus Medical Incorporated, US) that can impose rotational perturbations in the anteroposterior direction to the subjects. SOT has been widely used in healthy subjects [23, 24], in subjects with vestibular dysfunctions [25, 26] and in MS patients, to elucidate specific postural responses related to MS severity [27, 28] and to investigate the benefits of the rehabilitation treatments [10]. Di Fabio et al [25] used SOT to detect vestibular deficits, finding a correlation between balance performances and vestibular impairment, as well as Schwab et al [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards mechanical perturbation, instead, the most widespread test is the Sensory Organization Test (SOT, NeuroCom, Natus Medical Incorporated, US) that can impose rotational perturbations in the anteroposterior direction to the subjects. SOT has been widely used in healthy subjects [23, 24], in subjects with vestibular dysfunctions [25, 26] and in MS patients, to elucidate specific postural responses related to MS severity [27, 28] and to investigate the benefits of the rehabilitation treatments [10]. Di Fabio et al [25] used SOT to detect vestibular deficits, finding a correlation between balance performances and vestibular impairment, as well as Schwab et al [26].…”
Section: Introductionmentioning
confidence: 99%
“…SOT has been widely used in healthy subjects [23, 24], in subjects with vestibular dysfunctions [25, 26] and in MS patients, to elucidate specific postural responses related to MS severity [27, 28] and to investigate the benefits of the rehabilitation treatments [10]. Di Fabio et al [25] used SOT to detect vestibular deficits, finding a correlation between balance performances and vestibular impairment, as well as Schwab et al [26]. Fjeldstad et al [27] tested SM subjects by using SOT and showed significant differences on postural stability between MS and control groups and a good correlation between the standard Berg Balance Scale BBS and the SOT score.…”
Section: Introductionmentioning
confidence: 99%
“…Um aspecto que poderia justificar os resultados obtidos na presente pesquisa, principalmente, os dados relacionados ao grupo de escolares surdos, são os achados de Horak et al (27), que avaliaram 42 crianças com perda auditiva sensório-neural e relataram que anormalidades na função do sistema vestibular podem ser observadas de 49 a 95% nestas crianças, nas provas calóricas e rotatórias, nas quais estão envolvidos os canais semicirculares horizontais, núcleos vestibulares, núcleo e músculos oculomotores, responsáveis pela regulação do controle postural. Outras pesquisas também informam que a hipoatividade do sistema vestibular é um achado frequente em avaliações otoneurológicas em crianças com perda auditiva sensório-neural (28,29). Tais dados poderiam justificar a alta ocorrência de alterações posturais no grupo dos escolares surdos deste estudo, visto que o sistema vestibular é um dos três sistemas sensoriais responsáveis pela regulação do controle postural.…”
Section: Discussionunclassified
“…The low-quality study by Zhou et al (19) reported a prevalence of 91.3% for saccular dysfunction through VEMP testing. The fair quality studies (40,47,49,53,54), reported a prevalence of semi-circular canal abnormality between 5 and 58.8%. Only one fair quality study (47), reported a hyperfunction of 3%.…”
Section: Snhlmentioning
confidence: 99%